2016
DOI: 10.1016/j.eurpsy.2016.01.2424
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional default mode network and executive control network in people with Internet gaming disorder: Independent component analysis under a probability discounting task

Abstract: The results suggest that people with IGD show altered modulation in DMN and deficit in executive control function, which might be the reason for why the IGD subjects continue to play online games despite the potential negative consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 61 publications
(63 reference statements)
5
30
0
Order By: Relevance
“…Inclusion criteria for the IGD group were the following: (1) scored larger than 50 on Young’s IAT (Lin et al, 2015a,b; Wang L. et al, 2016a,b); (2) met at least 5 DSM-5 criteria; (3) play online games is their major Internet activity; (4) play online games more than 14 h per week, for a minimum of 2 years; (5) endorsement of League of Legends (a popular online game in China) as the only source of Internet online games. The inclusion of RGU is the key step of the current study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion criteria for the IGD group were the following: (1) scored larger than 50 on Young’s IAT (Lin et al, 2015a,b; Wang L. et al, 2016a,b); (2) met at least 5 DSM-5 criteria; (3) play online games is their major Internet activity; (4) play online games more than 14 h per week, for a minimum of 2 years; (5) endorsement of League of Legends (a popular online game in China) as the only source of Internet online games. The inclusion of RGU is the key step of the current study.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it has been noted that IGD subjects are associated with failures in controlling the desire for playing online games (Lin et al, 2015a). Numerous imaging studies have found impaired executive control ability in IGD subjects (Dong and Zhou, 2010; Dong et al, 2010, 2011b, 2012a, 2014b, 2015, 2017b; Dong and Potenza, 2014; Weinstein and Lejoyeux, 2015; Wang L. et al, 2016a,b; Wang Y. et al, 2016b; Weinstein et al, 2017), yet, the direct evidence for the impaired executive control ability in inhibiting craving for game-playing in the context of online gaming cues are still lacking (Ko et al, 2008, 2013; Han et al, 2010; Sun et al, 2012). Thus, the present study filled in the gap.…”
Section: Introductionmentioning
confidence: 99%
“…Because of an increased reward sensitivity and decreased lack of considering losses, 8,216,217 as well as deficient response inhibition 218,219 and executive control, 80 the authors speculated that deficient cognitive control in association with enhanced reward seeking would lead to increased gaming. Gamers exhibit deficiencies in impulse control, attentional capabilities, 220-222 overall cognitive functioning, 8,223 and impaired risk perception, 224 favouring risky decisions because they strive for immediate positive rewards and neglect negative long-term consequences for social or work domains in real life. 225 The multi-disciplinary aetio-pathogenetic model of Dreier et al 226 and M€ uller et al 227 includes psychological (e.g.…”
Section: Complex Modelsmentioning
confidence: 99%
“…All studies on decision-making among problematic gamers show similar findings that problematic gamers have impaired decision-making [40,50,51,53,54]. Furthermore, it appears that the excessive gamers tend to make riskier choices [50,54], which could explain their tendency to play videogames more than intended (e.g., playing more despite being more tired the next day).…”
Section: Discussionmentioning
confidence: 56%
“…Two studies have explored risky decision-making using the Probability Discounting Task (PDT) performance of IGD participants in group analysis [50,51]. Both studies recruited 40 participants distributed equally in two groups (i.e., IGD players vs. controls) of 20 participants.…”
Section: Decision-makingmentioning
confidence: 99%